Evolución histórica de la teoría del bien jurídico penal - Espinosa Leal, Idalia Patricia (Archivos de criminología, seguridad privada y criminalística, 2022)
In this article we will see the historical evolution of the idea of crime and its basis for the application of punishment, addressing the most relevant theories that appeared during the course of time, such as: the theory of subjective rights, the theory of legal good , the legalconstitutional theory, the functionalist theory and the personalist theory; It should be noted that as the lines of thought emerged, it cannot be considered that they fully displaced the previous one, rather in each of these stages the coexistence of opposing ideas persisted.